Inflammatory Conditions in Acute Coronary Syndrome Patients Treated with Percutaneous Coronary Intervention of Saphenous Vein Graft - Cankurt, Tayyar (Int J Angiol, 2020)
The study aimed to evaluate the inflammatory blood parameters in acute coronary syndrome (ACS) patients with a history of coronary artery bypass graft (CABG) and treated with percutaneous coronary intervention (PCI) of saphenous vein graft (SVG). A total of 347 patients who underwent urgent SVG PCI with the diagnosis of ACS were included in the study. After the application of exclusion criteria, 79 patients were allocated into two groups, namely, successful PCI ( n  = 59) and unsuccessful PCI ( n  = 20), and included in the statistical analysis. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) levels were significantly higher in patients with unsuccessful SVG PCI. In the logistic regression analysis, PLR, C-reactive protein, and diabetes mellitus emerged as independent factors associated with unsuccessful SVG PCI. The area under the curve for PLR was 0.70 (95% confidence interval: 0.55–0.85, p  = 0.006). The cut-off value of PLR (128.99) was associated with 70.0% sensitivity and 69.5% specificity. Elevated inflammatory status is associated with unsuccessful PCI of SVG in ACS patients. Increased PLR levels on admission is an independent predictor of this situation. This cheap and simple marker can help us to predict unsuccessful SVG PCI in ACS patients.